Deep neck space infections: comparison of outcomes between diabetic and non-diabetic patients - Ashokan, Sona; Rajan, K. V.; T., Santhi (International Journal of Research in Medical Sciences, 2021)
Background: The objective of the study was to study the clinical presentation, microbiological profile, treatment protocol of deep neck space infections in diabetics and non diabetics. Methods: This was a prospective study conducted on 76 patients (diabetics and non diabetics) admitted in the Department of Otorhinolaryngology, TD Medical college, Alappuzha over a period of 18 months from January 2012 to June 2013. Results: The age distribution was 15-75 years. Male to female ratio was 2:1. Fever, pain, neck swelling and odynophagia were the common symptoms with dyspnoea and chest pain indicative of complications. The most common etiology was odontogenic (68.4%) followed by tonsillopharyngeal infection and foreign bodies. No etiological factor was found in 34.2%. The commonest site was submandibular space (64.2%) followed by parapharyngeal space (26.6%). Abscess was present in majority needing surgical drainage. The most common organism isolated was streptococcus viridans (37.5%). Preponderance of klebsiella species was noted in diabetics. Streptococcus showed susceptibility to pencillin (83.33%), ampicillin (92%), cefotaxime (60.526%). Klebsiella showed susceptibility to gentamicin (42.3%) and ciprofloxacin (28.57%). The complication rate was more in diabetics (34.21%). Contrast enhanced CT was done in cases suspected to have complication. The mean hospital stay was longer in diabetics (19.6 days) than non diabetics (6.4 days). Conclusions: Deep neck space infection still remains life threatening if not heeded promptly. Senescence and diabetes demand surgical intervention and meticulous glycemic control to prevent complications. Judicious use of antimicrobials and timely radiological and surgical interventions have come a long way in the management and in providing a cure to this dreaded condition.